2019
DOI: 10.1002/jtr.2310
|View full text |Cite
|
Sign up to set email alerts
|

Disaster risk, risk management, and tourism competitiveness: A cross‐nation analysis

Abstract: This study explored how disaster risk and risk management level affect a country‐s tourism competitiveness using a classification of two dimensions of disaster risk, namely, exposure and vulnerability. We analyze empirical data from 128 countries in 2013 and find that both exposure to natural disasters and vulnerability can reduce a country‐s ability to compete globally in the tourism and a higher risk management level can improve its competitiveness. Additionally, government effectiveness moderates the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…In their theoretical review on tourism risk, Williams and Baláž (2015) argue that the industry is especially vulnerable to exogenous hazards, such as natural and sociopolitical disasters, and they outline that important risks exist at all industry levels, from the firm level to the destination level and the nation-wide level. Risk management hence has a crucial role in tourism competitiveness ( Liu, Cheng, & OuYang, 2019 ).…”
Section: Tourism and Pandemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their theoretical review on tourism risk, Williams and Baláž (2015) argue that the industry is especially vulnerable to exogenous hazards, such as natural and sociopolitical disasters, and they outline that important risks exist at all industry levels, from the firm level to the destination level and the nation-wide level. Risk management hence has a crucial role in tourism competitiveness ( Liu, Cheng, & OuYang, 2019 ).…”
Section: Tourism and Pandemicsmentioning
confidence: 99%
“…Similar to the non-tourism literature ( Noy & Yonson, 2018 ), the concept of tourism disaster risk and vulnerability are closely related ( Liu et al, 2019 ). Vulnerability refers to “the conditions determined by physical, social, economic and environmental factors or processes which increase the susceptibility of an individual, a community, assets or systems to the impacts of hazards” ( UNDRR, 2020 ).…”
Section: Tourism and Pandemicsmentioning
confidence: 99%
“…In 1999, there was a sharp decrease (2,605 million USD) in the tourism income. Liu et al (2019) indicated that the tourism competitiveness of a country is shaped Studies emphasize the perceived risks of tourism industry service providers, and also the effect of crisis risk management on the competitive advantage of tourism. Mistilis and Sheldon (2006) stated that the tourism industry is fragmented and does not respond easily to disasters.…”
Section: Earthquake and Tourism Sector In Turkeymentioning
confidence: 99%
“…Therefore, once a disaster occurs, which would cause great loss to both tourists' life and property, heavily damaged the development of local tourism and brought a destructive influence in a long period of time(Y. Liu, Cheng, & Ouyang, 2019). More and more scenic spots are interested in disaster management systems, but how to conduct system design and data governance are still being explored.Therefore, it is necessary to establish an integrated environmental disaster database management, evaluation and emergency response system.…”
Section: Introductionmentioning
confidence: 99%